Validation of a (peer) feedback perceptions questionnaire - Strijbos, Jan-Willem; Pat-El, Ron J.; Narciss, Susanne (Proceedings of the International Conference on Networked Learning, 2010)
A core educational goal is to produce self-directed lifelong learners who have acquired or are able to acquire the knowledge and skills necessary for their future professional workplace in a networked world. Constructivist and socio-constructivist theories of learning and instruction recommend using collaborative learning scenarios in all kinds of educational contexts in order to attain this goal. Thus, (networked) collaborative learning receives increasing attention in Higher and Further Education. To empower students as self-regulated and collaborative learners peer assessment and peer feedback are increasingly applied in both networked and face-to-face collaborative learning environments. Thus, the conditions under which peer feedback is beneficial for students’ learning are worth to be investigated in detail. While the efficiency of feedback content has received much attention in prior feedback research, students’ feedback perceptions have been hardly studied. In addition, students’ emotional state can mediate the impact of (peer) feedback on their performance. Yet, each kind of feedback has to be perceived and processed in a mindful way, that is, attended to, understood and interpreted, and finally transformed into a corrective action by the student before it can influence subsequent learning. Since up to now the issue of feedback perception has been a neglected area of feedback research, instruments for measuring feedback perceptions are lacking. The purpose of this paper is thus to describe the development and the structural validation of a feedback perception questionnaire which measures students’ feedback perceptions in terms of fairness (FA), usefulness (US), acceptance (AC), willingness to improve (WI) and affect (AF). The sample consists of 1535 secondary education students. They received a scenario in which a fictional student received fictional peer feedback on a writing assignment and this feedback was Concise General (CGF) or Elaborated Specific (ESF). The students’ were asked to rate their perception of the feedback as if they had received the feedback themselves. The analyses confirm the structural validity of the five scales. FA, US and AC constitute the joined second order component ‘Perceived Adequacy of Feedback’ (PAF), which in turn positively predicts willingness to improve (WI) and affect (AF). The scale reliabilities were good to excellent.